Sensitivity of the Cogstate Test Battery for Detecting Prolonged Cognitive Alterations Stemming From Sport-Related Concussions. Issue 1 (January 2019) - Sicard, Veronik; Moore, Robert D.; Ellemberg, Dave
Abstract : Objective: To determine if the Cogstate test battery contains the requisite sensitivity to detect prolonged cognitive alterations. Methods: One hundred twenty collegiate athletes (71 with a history of concussion; 49 controls) completed the Cogstate test battery, to which we added a 2-back condition. In addition to the Cogstate clinical (transformed variables), we analyzed the raw data. Results: The clinical variables failed to reveal any group differences. Further, although the raw data failed to reveal group differences for tasks measuring lower-level cognition, group differences were observed for accuracy on the 1- and 2-back tasks, which require multiple aspects of higher cognition. The overall classification accuracy was higher using the raw data than the clinical variables. The combined sensitivity of the 1- and 2-back task was moderate and specificity was high. Conclusions: These results suggest that using the raw scores over clinical variables increases the sensitivity of the test battery. Moreover, these results add another piece of evidence suggesting that concussive injuries are associated with subtle long-term alterations in aspects of higher cognition. Importantly, these deficits would have gone unobserved if we had relied solely on automated clinical variables. The current results further our scientific understanding of concussion and may be used to advance clinical practices. Abstract : Supplemental Digital Content is Available in the Text.